Juvenile justice–involved Haitian families' experiences of structural racism and socioethnic discrimination. Issue 5 (31st October 2022) - Cela, Toni; Demezier, Danna; Waldman, Rachel; Clement, Roy; Dembo, Richard; Jean‐Gilles, Michèle; Hogue, Aaron; Arcayos, Alexandra; Santisteban, Daniel; Marcelin, Louis Herns
Abstract: Objective: This article examines how Haitian families with youth interfacing with the juvenile justice system cope with structural racism and socioethnic discrimination (RSD). Background: Haitian families' experiences of discrimination based on their histories, immigrant status, and positionality illustrates the need for more scientific scrutiny of the experiences of RSD among Black immigrant groups. This National Institute on Drug Abuse (NIDA)–funded study details the narratives of and responses to RSD experienced by Haitian families interfacing with the juvenile justice system. Method: Data are drawn from psychosocial assessment tools, therapeutic sessions, and ethnographic interviews conducted with Haitian families participating in a family‐based therapeutic intervention. Using critical race theory, we foreground the voices of those negatively impacted and use Bourdieu's theory of practice to examine the intersectionality of race and ethnicity in this population's experiences of RSD. Results: The different experiences of and responses to RSD among youth and caregivers of Haitian descent are both a variation of the complex continuum of structural racism in the United States and unique to their immigrant experience of marginalization and cultural invalidation by public institutions, community members, and peers. Conclusion: Professionals working with this population must be sensitive to the ways these experiences impact young people's identity development processes, their health, and well‐being. Haitian caregivers should be encouraged to protect their children by engaging in racial and socioethnic socialization that validates their RSD experiences. Implications: Understanding the intergenerational experiences of RSD among Black, immigrant groups and encouraging family dialogue and adolescent support will strengthen family cohesion during this period of racial reckoning.